Answer:
x = -4
Step-by-step explanation:
The given expression:
-4x - 7 - 3x + 4 = 25
To solve this expression, the first thing you do is to collect like terms. We'll bring x together as well as constant on the left side of the equation.
-4x - 3x - 7 + 4 = 25
Then we would take the constants on the left to the right side of the equation. Note that when you move a number to the other side of the equation, the sign changes.
-4x - 3x = 25 + 7 - 4
Then we solve
-7x = 28
divide both sides by -7
![\begin{gathered} (-7x)/(-7)=\text{ }(28)/(-7) \\ x\text{ = -4} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/iwmhveqfjel8tkwp0v66vnnwhry18mna1w.png)
The final answer : x= -4